Impairment, disability and fatigue in multiple sclerosis - Shahnaz Shahrbanian; Pierre Duquette; Nancy Mayo (Babol University of Medical Sciences, 2018)
Background: Identifying the predictors of pain is important for both health professionals and researchers, because pain has repeatedly been found to be a strong predictor of activity limitations and participation restrictions. The objective of this study was to determine the predictors of pain presence and severity in a large, well-designed sample of community dwelling individuals with multiple sclerosis (MS). Methods: This was a cross-sectional study. A center-stratified random sample including 188 persons with MS were recruited from three major MS clinics in the Greater Montreal, Canada. Main outcomes included pain prevalence and severity. Predictor variables included depression, anxiety, perceived health status, fatigue, sleep problems, and perceived cognitive deficits. Participants completed three questionnaires: the first asked about the socio-demographic and clinical information of the subjects, the second assessed the pain characteristics of the subjects, and the third covered the predictor variables. Results: The prevalence of pain in our sample was 42%. MS- related disability was found to be in the main predictor for both pain presence and intensity. Fatigue also was a main contributor to pain presence. The results of this study also showed that pain was associated with higher levels of depression, anxiety, sleep problems, and perceived cognitive deficits, and diminished perceived health status. Conclusions: The results of this study indicated that pain is a common symptom among people with MS. Pain presence was predicted by MS-related disability and fatigue, while pain intensity was only predicted by MS severity.